Halofuginone, a Specific Inhibitor of Collagen Type 1 Synthesis, Ameliorates Oxidant Colonic Damage in Rats with Experimental Colitis - YEGEN, BERRAK; ERCAN, FERİHA; YÜKSEL, MERAL (SPRINGER, 2010)
To evaluate the effect of halofuginone on trinitrobenzene sulfonic acid (TNBS)-induced colonic injury, rats were given halofuginone (40 mu g/kg, intraperitoneally) or saline 1 h before the induction of colitis, and the injections were continued twice daily for 3 days until they were decapitated. High macroscopic and microscopic damage scores, elevated colonic wet weights, colonic myeloperoxidase activity, malondialdehyde and tissue collagen level, and luminol chemiluminescence values, and marked reduction in glutathione level of the saline-treated colitis group were all reversed by treatment with halofuginone. In conclusion, halofuginone exerts beneficial effects in TNBS-induced colonic inflammation in rats. The anti-inflammatory effects of halofuginone appear to involve suppression of neutrophil accumulation, preservation of endogenous glutathione, and inhibition of reactive oxidant generation. Halofuginone also shows antifibrotic effect via inhibition of tissue collagen production. The present data encourage possible use of the antifibrotic halofuginone as an anti-inflammatory agent in improving oxidative injury in colitis.
Keywords: Halofuginone; Colitis; Trinitrobenzene sulfonic acid (TNBS); Oxidant damage; Collagen; INFLAMMATORY-BOWEL-DISEASE; I SYNTHESIS; CROHNS-DISEASE; ULCERATIVE-COLITIS; CELL-PROLIFERATION; FIBROSIS; FIBROBLASTS; EXPRESSION; STRICTURES; INJURY